The Complete Rankin/Bass Christmas collection [videorecording (Blu-Ray)] - Bass, Jules (Universal Studios, 2023)
"'Tis the season to enjoy the timeless holiday favorites in The Classic Christmas Specials Collection featuring three unforgettable stories. Produced by Rankin/Bass, Rudolph the Red-Nosed Reindeer and Santa Claus is Comin' To Town feature iconic ""Animagic"" stop-motion animation and Frosty the Snowman is beautifully animated. Starring the voice talents of Fred Astaire, Jimmy Durante, Mickey Rooney, Burl Ives and many more, these favorites also feature some of the most beloved songs of the season and are sure to entertain audiences of all ages for generations to come!"